2006
DOI: 10.1515/jpm.2006.002
|View full text |Cite
|
Sign up to set email alerts
|

A sonographic short cervix as the only clinical manifestation of intra-amniotic infection

Abstract: Objective: A sonographically short cervix is a powerful predictor of spontaneous preterm delivery. However, the etiology and optimal management of a patient with a short cervix in the mid-trimester of pregnancy remain uncertain. Microbial invasion of the amniotic cavity (MIAC) and intra-amniotic inflammation are frequently present in patients with spontaneous preterm labor or acute cervical insufficiency. This study was conducted to determine the rate of MIAC and intra-amniotic inflammation in patients with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
0
10

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(143 citation statements)
references
References 54 publications
6
127
0
10
Order By: Relevance
“…Of those, 40% delivered before 32 weeks [53], underlying the relationship between inflammation/infection and sPTB.…”
Section: Patient Obstetrical and Medical Historymentioning
confidence: 99%
“…Of those, 40% delivered before 32 weeks [53], underlying the relationship between inflammation/infection and sPTB.…”
Section: Patient Obstetrical and Medical Historymentioning
confidence: 99%
“…However, ultrasound can be used to safely assess cervical status in PPROM patients (12,29), and cervical length as determined by transvaginal ultrasonography in PPROM patients might predict the interval between admission and delivery (12,13,29). Moreover, recently, it has been reported that cervical length measurement usefully predicts microbial invasion of the amniotic cavity in women with preterm labor and intact membranes (14,15). In the present study, it was found that cervical length is a sensitive marker (sensitivity 85%; specificity 65%) of the presence of intra-amniotic microbial invasion in PPROM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Iams et al found that a short cervix during pregnancy is an independent risk factor of the subsequent developments of clinical chorioamnionitis and neonatal sepsis (30). Hassan et al concluded that a short cervix is a clinical manifestation of intra-amniotic infection (14), and Gomez et al reported that a short cervix in women with preterm labor and intact membranes is a risk factor for microbial invasion of the amniotic cavity (15). Moreover, it has been reported that a short cervix in women with PPROM is a risk factor of imminent delivery (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embarazo con algunas de las siguientes condiciones clínicas presentes sugerentes de infección intrauterina: RPM, corioamnionitis clínica, sangrado vaginal con desprendimiento amniocorial, infección cér-vicovaginal (ICV) especialmente por Streptococcus Grupo B (SGB), infección del tracto urinario (ITU), dispositivo intrauterino (DIU) no extraí-do, placenta previa con sangrado vaginal, cérvix menor de 15 mm medido por ultrasonografía, desprendimiento prematuro de placenta normoinserta (DPPNI), membranas prolapsadas bajo el orificio cervical externo (MPr) [25][26][27][28][29][30][31][32] y asociado con los siguientes marcadores histopatológicos placentarios específicos: corioamnionitis aguda, funisitis aguda [5][6][7][8][9][10][11][12] . b) Enfermedades maternas Hipertensión arterial.…”
Section: ) Maternosunclassified